Co-located ecological data for exploring top- and subsoil carbon dynamics across grassland-woodland contrasts - Reinsch, Sabine; Lebron, Inma; Brentegani, Michele; Brooks, Milo; Busi, Susheel Bhanu; Cagnarini, Claudia; Cooper, David; Day, John; Emmett, Bridget A.; Fitos, Eleonora; Goodall, Tim; Griffiths, Robert; et al. (Scientific data, 2024)
Soil organic carbon (SOC) is a soil health indicator and understanding dynamics changing SOC stocks will help achieving net zero goals. Here we present four datasets featuring 11,750 data points covering co-located aboveground and below-ground metrics for exploring ecosystem SOC dynamics. Five sites across England with an established land use contrast, grassland and woodland next to each other, were rigorously sampled for aboveground (n = 109), surface (n = 33 soil water release curves), topsoil, and subsoil metrics. Commonly measured soil metrics were analysed in five soil increments for 0–1 metre (n = 4550). Less commonly measured soil metrics which were assumed to change across the soil profile were measured on a subset of samples only (n = 3762). Additionally, we developed a simple method for soil organic matter fractionation using density fractionation which is part of the less common metrics. Finally, soil metrics which may impact SOC dynamics, but with less confidence as to their importance across the soil profile were only measured on topsoil (~5–15 cm = mineral soil) and subsoil (below 50 cm) samples (n = 2567).